Factors affecting energy security - Ruixue, Shao (Экономика и банки, 2024)
Energy security is a major challenge facing the world today. With the rapid development of the global economy, the demand for energy is growing, and the uneven distribution of energy resources and the uncertainty of supply make energy security increasingly prominent. Taking Northeast Asia as the research object, this paper studies the evolution and connotation development of energy security, and studies three important theoretical bases of energy security: resource scarcity theory, geopolitical theory and sustainable development theory of energy security. The energy import and export volumes, the development and application of various types of energy sources, and the percentage of energy consumption categories in Northeast Asian countries were analyzed. Through the analysis of these indicators, we can reflect the factors affecting energy security and explore how to jointly ensure energy security in Northeast Asia.The conclusion is that the path of energy development is to develop towards diversified energy supply and transform towards environmental friendliness.